O leitor imerso em aplicativos tecnológicos literários: uma interação hipertextual/hipermidiática - Paz, Keli Almeida Bortoli (2013)
This study addresses the involvement of children and adolescents with literary interactive applications, available in cyberspace, with analysis three different stories The butterfly flying , Cinderella and The three little pigs . The research analyzes the interaction of these new readers with the intention to assess and describe the profile of reading hypertext and hipermidial from the digital platform of Ipad. The proposal is based on the precepts of cyberculture theorists Lévy (2010), the immersive digital reader proposed by Santaella (2007), about the prospect of generation Homo Zappiens defended by Veen & Vrakking (2009). The methodological procedure is characterized by a case study, as Gil (2009), and addresses the issues in qualitative way immersion readers. Users hold the digital environment navigations collaboratively, from games, but have no concern in interpreting the content, which reveals a surface navigation. Young people show know cyberspace, although declare initially the only environment that literary reading was printed. Found, from the literary applications, a new way to explore cyberspace and contact reading, standing as co-authors of the works, because the interaction with the applications allowed the characters move and manipulate audiovisual effects. The works were analyzed in different ways by the individuals who shared their experiences of reading. The research findings show the reader the digital environment that, after seeing the applications of interactive literary texts, reading develops through hypertext and hypermedia and starts to act by means of navigation in cyberspace, reflexively changing its positioning in for some interactions with other applications